Abs. Issue 1 (November 2015) - Rybko, V.; Khromova, N.; Farmakovskaya, M.; Novikova, M.; Kopnin, B.; Kopnin, P.
Abstract : Malignant tumors consist not only of neoplastic cells, but also of various normal cells, for example fibroblasts, macrophages or endothelial cells. These normal cells stand under constant pressure of transformed cells, regulating their properties and converting them into tumor-promoting cells. Tumor-stroma interaction takes place during all stages of carcinogenesis. Notch activation upon receptor binding with the ligand is a way of direct intercellular communication during embryo- and histogenesis, determining various processes like differentiation, proliferation, etc. It has been previously shown that in tumors this signaling cascade regulates not only properties of transformed cells, but also stromal cells activities, i.e. neoangiogenesis. The Notch role in communication between neoplastic cells and stromal fibroblasts is underinvestigated. Cancer-associated stromal fibroblasts (CAFs) are an important component of tumors secreting growth factors and proteases, modulating immune reactions and contributing to cancer stem cells niches formation. CAFs resemble myofibroblasts and express α Smooth-Muscle Actin ( α SMA). We obtained and characterized cultures of normal mesenchymal cells: a myofibroblasts-like (MF), and fibroblasts-like MC1 and MC2, differing by Notch1 expression. These cell cultures variously influenced growth of colon cancer notch- ligand Jagged2-positive HCT116 xenographs in nude mice. MF cells were characterized by the strongest while Notch1-deficient MC2 by the weakest tumor-promoting activity. MC1 but not MC2 started to express α SMA upon co-cultivation in vitro with neoplastic HCT116 cells. Such co-cultivation also lead to Notch activation according to a luciferase reporter. NICD (Notch Intracellular Domain) expression activated MC1 and MC2, while Notch1 silencing in MC1 abrogated both HCT116-mediated activation of the fibroblasts in vitro and their tumor-promoting activity in vivo. Notch signaling in mesenchymal cells stimulated TGFb production that lead to both autocrine and paracrine receptors stimulation. We believe that this cytokine activates fibroblasts in our experimental system. We also revealed that this process was p53-dependent. So we have shown Notch1 to be involved in tumor-stroma interaction, particularly its activation leading to fibroblasts transdifferentiation. Notch1-stimulated fibroblasts are able to produce TGFb and to promote tumor growth in xenographs. The tumor-stimulating potency of various fibroblasts in our experimental system depends on their ability to transdifferentiate to myofibroblasts upon Notch activation.